A volume-of-fluid ghost-cell immersed boundary method for multiphase flows with contact line dynamics. (30th March 2018) - O'Brien, Adam; Bussmann, Markus
Highlights: A new contact line model for ghost-cell immersed boundary methods is proposed. The contact line model is suitable for flat and curved geometries. Some applications of the model are demonstrated. A coupled momentum/CICSAM scheme is proposed for high density ratio flows. Abstract: A method is proposed for modelling contact line dynamics in volume-of-fluid frameworks using a common and robust ghost-cell immersed boundary method in 2D. The method implements a contact line model based on the CELESTE method, used in conjunction with a CICSAM scheme capable of handling multiphase flows in which the phases have large variations in their physical properties. The ability of the model to resolve contact lines on both planar and curved geometries is demonstrated. It is also shown that the model maintains good mass conservation. Dynamic cases studied include a planar water droplet impact onto a cylinder, as well as a planar droplet penetration into a bank of cylinders with varying hydrophobicity.